LINGUISTIC ANALYSIS OF THE CONCEPT "FORGIVENESS" - Dilnoza Sharafutdinov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
An article presents a lexical-semantic interpretation of the concept of "forgiveness". As an introductory point in the systematic analysis of the concept of "forgiveness", this provides a practical explanation of forgiveness. Indeed, saying "sorry" is an expression of sorrow for doing anything that has upset or troubled someone. To every one of us, forgiveness will mean something different. But generally speaking, it entails choosing to consciously let go of bitterness and rage. You can never truly go over an act that insulted or injured you. However, you may decrease the impact of this conduct on yourself by practicing "forgiveness". According to some linguists, it's a way to make corrections. Apologizing involves taking action or expressing oneself with the intention of correcting the situation.